Lactococcus lactis D4 Has Potential Effect to Alleviate Inflammation and Reverse Dysbiosis in Colitis Rat Model - Suswita, Rini; Alvarino, Alvarino; Darwin, Eryati; Jamsari, Jamsari (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Inflammatory bowel disease (IBD) is a prevalent chronic inflammatory disorder of the gastrointestinal tract that may lead to colorectal cancer if untreated. Several medications for IBD have adverse side effects. Thus, there are high interest for searching alternative treatment to treat IBD. Lactococcus lactis D4 isolated from dadih, a traditional fermented buffalo milk product, was investigated for the effect on gut inflammation and microbial composition in the colitis rat model.METHODS: Eighteen male Sprague-Dawley rats were divided into three groups; control rats, colitis-induced rats, and colitis-induced rats treated with L. lactis D4 isolate. The control group received water, while the colitis-induced rats were given azoxymethane (AOM) and dextran sodium sulphate (DSS). Rats’ feces were collected for the analysis of gut microbiota diversity by next-generation sequencing and for the measurement of transforming growth factor (TGF)-β, nuclear factor kappa-B (NF-κB), interleukin (IL)-6, and tumor necrosis factor (TNF)-α colonic expression using reverse transcription-quantitative polymerase chain reaction (RT-qPCR).RESULTS: L. lactis D4 administration was able to reduce inflammation in colitis by decreasing IL-6 expression (0.87 vs. 0.73), while expression of TGF-β, NF-κB, and TNF-α were increased compared to the model group, suggesting a complex immunomodulatory effect. Gut microbiota sequencing revealed a similarity between the control and treatment groups, suggesting L. lactis D4 has great potential to ameliorate gut microbiota dysbiosis in colitis rats.CONCLUSION: L. lactis D4 has a beneficial effect in decreasing pro-inflammatory cytokines and is able to reserve dysbiosis in colitis rat model. Thus, L. lactis D4 might be used as a therapeutic agent for IBD.KEYWORDS: colitis, gut microbiota, inflammation, inflammatory bowel disease, Lactococcus lactis D4, probiotic, proinflammatory cytokines